Geometric influence on intramolecular photoinduced electron transfer in platinum(II) acetylide-linked donor-acceptor assemblies - Molina-Ontoria, Agustin; Rivera-Nazario, Danisha M.; Tigreros, Alexis; Ortiz, Alejandro; Nunez, Jose E.; Insuasty, Braulio; Lüders, Daniela; Wolfrum, Silke; Guldi, Dirk Michael; Echegoyen, Luis (Chemistry - A European Journal, 2014)
A new donor-acceptor system, in which the electron donor triphenylamine (TPA) and the electron acceptor C60 are bridged through a cis- or trans-platinum(II) acetylide spacer have been prepared. Ground-state studies were conducted using electrochemistry and UV/Vis spectroscopy. Fluorescence studies suggested that charge transfer is the deactivation mechanism for the singlet excited state, and this was verified by transient absorption spectroscopy. Selective photoexcitation of 1 and 2 at 387 nm leads to a fast charge transfer between the TPA and C60, which gives rise to a radical ion-pair state (TPA.+-Pt-C60.-). Our results suggest that charge transfer is favored for the cis configuration while the presence of the trans configuration in the PtII diacetylide results in a longer-lived charge separated states. © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-03-07
Keywords: electron transfer; excited states; fullerenes; platinum(II) acetylide; triphenylamine